2022
DOI: 10.1039/d2ta00068g
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth of crystalline carbon nitride on LaOCl for photocatalytic overall water splitting

Abstract: Photocatalytic overall water splitting is an ideal pathway to store solar energy, and produce clean and sustainable hydrogen fuel. However, exploring photocatalytic materials with high efficiency for overall water splitting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…43 And compared with O 2 (0.82 V), the oxidation product of water, both HOMO potentials were relatively positive. 44 The above test results indicated that the synthesized materials were theoretically feasible for photocatalytic CO 2 reduction and water oxidation. And anchoring the Zn SAs may be favorable for photocatalytic CO 2 reduction due to the expansion of optical absorption.…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 78%
“…43 And compared with O 2 (0.82 V), the oxidation product of water, both HOMO potentials were relatively positive. 44 The above test results indicated that the synthesized materials were theoretically feasible for photocatalytic CO 2 reduction and water oxidation. And anchoring the Zn SAs may be favorable for photocatalytic CO 2 reduction due to the expansion of optical absorption.…”
Section: Synthesis and Structural Characterizationmentioning
confidence: 78%
“…The high crystallinity of g-C 3 N 4 is favorable for the transport of photoexcited charges, and the built-in electric field formed at the hetero-interface can promote the separation of excited electron-holes, thereby inhibiting their recombination, and finally achieving a good photocatalytic performance. 146 In addition, the heterojunctions with different crystal phases of the same material can remarkably eliminate the interfacial defects. 144,147,148 The built-in electric field formed by this close contact heterogeneous interface (Fig.…”
Section: Construction Of Heterojunctionsmentioning
confidence: 99%
“…4,5 Among numerous researched semiconductor photocatalysts, graphitic carbon nitride (CN) has been drawing increasing interest in photocatalytic H 2 evolution, pollutant degradation, N 2 xation and CO 2 reduction, owing to its easy manufacture, low cost, highly exible structure, visible-light response, and good thermal and chemical stabilities. 6,7 Recently, various strategies such as morphology control, 8,9 heteroatom doping, 10 and heterojunction construction 11 have been devised to enhance photoinduced electron-hole separation and then improve the photocatalytic activity of CN, owing to the intrinsically low dielectric properties of CN. Further studies reveal that the strong Coulomb interaction between the photoinduced electrons and holes in polymeric CN has been considered as one of the major factors that result in slow exciton dissociation and fast charge recombination and thus limit the photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%